Speaking for the Planet Earth: Toxicity and Environmental Responsibility in Rachel Carson’s Silent Spring - Bishnu Prasad Pokharel; Bal Krishna Sharma (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This study examines how Rachel Carson’s Silent Spring, an elementary environmental text, exposes the fatal consequences of indiscriminate use of pesticides for agricultural growth. The principal issue of the paper is to study how Silent Spring raises the issue of ecological degradation and the prime requirement to generate awareness for upholding biocentric interrelations. The main objective of this paper is to explore Carson’s environmental concern about the mindless exploitation of resources that threatens nature’s biodiversity and its regenerative potential induced by unethical human activities. Carson’s bold environmental stance shows how she critiques the abuse of chemical pesticides, engendering a massive destruction of the biodiversity that nature sustains. This paper argues that Carson’s book challenges the unethical and exploitative activities of human organizations for encouraging biocentric communities to use DDT and other detrimental pesticides for agricultural practices. The discussion is informed by the theoretical lens of Aldo Leopold’s land ethics. Leopold’s concept of land ethics holds that all life forms have a right to access land. Informed by the qualitative research design, the study applies an ecocritical perspective for analysis. The paper draws upon Silent Spring for the primary data and uses relevant journal articles and books for secondary information. The findings show that such unethical practices not only destroy all the necessary organisms of the earth but also vitiate humans’ natural capacity to sustain and thrive. The analysis concludes that technological development, industrialization, and commercialization have severed the natural bond between humans and nonhumans, alienating human beings from their organic lifestyle. Ultimately, this study recommends promoting symbiotic relations among all the members of the human community for sustainable development.